Automatic Determination of Parting Line Locations for Sand-Casting Process Using CAD System - Tama Reza Setiawan Putra; Fariz Muharram Hasby; Isa Setiasyah Toha; Wisnu Aribowo (IEEE Access, 2025)
The use of Computer Aided Design (CAD) technology is now playing an increasingly important role in determining the location of parting lines on cast objects. The most used approach is to use tools that are available in certain CAD software, such as SolidWorks Mold Tools or the use of solid parting method. Each approach taken is closely related to manual work which often requires special knowledge and requires a longer completion time, when compared to work that has been carried out automatically. The Slicing method that parallels to parting direction will provide a simple and effective algorithm to obtain flat parting line solution. However, the lack of criteria representing mouldability can result in decisions being made from incomplete information. This research prioritizes five criteria specifically for the sand-casting process, namely projected area, undercut (number of undercut), draw distance, dimensional stability and volume part in cope and drag which are applied to an algorithm to build an automatic system in the form of an Add-in type application in SolidWorks 2022. With the proposed algorithm it is found that the use of five criteria will provide a broader view in making decisions regarding the location of parting lines on cast parts.